Letter: statins and cirrhosis. Issue 11 (3rd November 2017) - Athyros, V. G.; Katsiki, N.; Mikhailidis, D. P.
Abstract : Linked Content This article is linked to Bang et al paper. To view this article visithttps://doi.org/10.1111/apt.14243 .